Changes in cytokine profile with immunotherapy in viral warts using purified protein derivative, mumps measles rubella vaccine, and mycobacterium w vaccine - Amrita Sil; Sayantan Dasgupta; Somodyuti Chandra; Adrija Datta; Arini Banerjee; Nilay Kanti Das (Wolters Kluwer Medknow Publications, 2021)
Background: Immunotherapy for wart employs ability of immune system to recognize certain viral, bacterial, and fungal antigens in previously sensitized individual inducing Type IV delayed-type hypersensitivity reaction (up-regulated Th1 cytokines IL-1, TNF-α, IFN-γ; down-regulated Th2 cytokines IL-10), not only to injected antigen but also against wart virus. Aims: To evaluate and compare the pattern of production of Th1 cytokines (IL-1, TNF-α, IFN-γ) and Th2 cytokines (IL-10) in patients receiving immunotherapy with purified-protein-derivative (PPD), Mycobacterium w (Mw), or mumps-measles-rubella (MMR) vaccine. Methods: The cohort study conducted on patients receiving immunotherapy with PPD, Mw, or MMR which was injected intradermally at baseline, repeated every 2 weeks for 6 doses?. Five-millilit?e?r blood was collected for evaluation of cytokines at baseline and 12 weeks of treatment. Blood was centrifuged to separate serum, stored at -80°C. Cytokines were measured by ELISA using a standard kit. Results: Nine participants in PPD group, 11 in Mw group, and 12 in MMR group completed the study. IL-1 was raised from baseline in all study arms and was significant in PPD group (P = 0.008). There was a predicted increase in IFN-γ in Mw and MMR groups but not in the PPD group. In the PPD group, IFN-γ was found to be down regulated. IL-10, a Th 2 cytokine was down regulated in all the groups at the study end from baseline, significantly so in the PPD group (P = 0.027) and MMR group (P = 0.001). TNF-α, being a Th1 cytokine was down regulated in all groups instead of an increase. In PPD group, IL-10 was significantly low at study end in patients who had complete resolution of warts. Limitations: Longer follow-up could not be done due to logistic issues. Conclusion: IL-1, TNF-α upregulation and IL-10 downregulation confirm that cytokine milieu plays an important role in wart immunotherapy. TNF-α has no contributory role. IL-10 can be used as a biomarker of complete response in PPD therapy.